Methanogenic archaea in subgingival sites: a review - Nguyen-Hieu, Tung; Khelaifia, Saber; Aboudharam, Gerard; Drancourt, Michel (APMIS : acta pathologica, microbiologica et immunologica Scandinavica, 2013)
Archaea are non‐bacterial prokaryotes associated with oral microbiota in humans, but their roles in oral pathologies remain controversial. Several studies reported the molecular detection of methanogenic archaea from periodontitis, but the significance of this association has not been confirmed yet. An electronic search was therefore conducted in MEDLINE‐Pubmed to identify all papers published in English connecting archaea and periodontal infections. Data analysis of the selected studies showed that five genera of methanogenic archaea have been detected in the subgingival microbiota, Methanobrevibacter oralis being the most frequently detected species in 41% of periodontitis patients and 55% of periodontal pockets compared to 6% of healthy subjects and 5% of periodontally‐healthy sites (p < 10−5, Chi‐squared test). Based on the five determination‐criteria proposed by Socransky (association with disease, elimination of the organism, host response, animal pathogenicity and mechanisms of pathogenicity), M. oralis is a periodontal pathogen. The methanogenic archaea load correlating with periodontitis severity further supports the pathogenic role of methanogenic archaea in periodontitis. Therefore, detection and quantification of M. oralis in periodontal pockets could help the laboratory diagnosis and follow‐up of periodontitis. Determining the origin, diversity and pathogenesis of archaea in periodontal infections warrants further investigations.